PELAKSANAAN PROGRAM PENDIDIKAN DAN PELATIHAN PRAJABATAN OLEH BADAN PENGEMBANGAN SUMBER DAYA MANUSIA (BPSDM) PROVINSI RIAU DI KABUPATEN KUANTAN SINGINGI TAHUN 2018 - Dika, Asmar; Tinov, M. Y. Tiyas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The Implementation of the Pre-service education and training program by Badan Pengembangan Sumber Daya Manusia (BPSDM) of Riau Province in Kuantan Singingi Regency in 2018 is  still not effective. This is indicated by the large number of government employees who have not optimally carried out their duties and roles as community servants. This study aims to find out: (1) material on national insights, the role and function of the State Civil Apparatus (ASN) and the position, obligations and rights of civil servants, and the mindset of ASN as a community service provided by BPSDM Riau Province; (2) the ability of participants in education and pre-service training in Kuantan Singing Regency related to national insight, the role and function of the State Civil Apparatus (ASN) and the position, obligations and rights of civil servants, and the mindset of ASN as a community service; and (3) effectiveness of the implementation of pre-service education and training programs by BPSDM Riau Province in Kuantan Singingi Regency. This research uses a qualitative method with a descriptive approach. Data collection techniques used were interview and documentation techniques. The results of the study can be concluded that: (1) material national insight provided by the political concept of the Indonesian nation which views Indonesia as an inseparable region (land-sea-air), which unites the nation and state as a whole in all areas of life including: politics , economic, socio-cultural and defense and security. Material on the role and function of the State Civil Apparatus (ASN) and the position, obligations and rights of civil servants is contained in Law Number 5 of 2014 concerning State Civil Apparatus. While the ASN mindset material as a community service is in the form of an ASN or PNS self concept; (2) the ability of the participants in the education and training of Kuantan Singing pre-service is in accordance with the material provided by BPSDM, but only a small portion of the material; and (3) the implementation of pre-service education and training programs by BPSDM Riau Province in Kuantan Singingi Regency is considered to be effective. Because the aspects given are considered appropriate for the needs of newly appointed civil servants.    Keywords: Implementation, Pre-service Education and Training Program, BPSDM